Phytochemical Characterization, In Vitro Antioxidant Activity, and Quantitative Analysis by Micellar Electrokinetic Chromatography of Hawthorn (Crataegus pubescens) Fruit - Francisco Erik González-Jiménez; Juan Alfredo Salazar-Montoya; Graciano Calva-Calva; Emma Gloria Ramos-Ramírez (Journal of Food Quality)
Due to their antioxidant properties, polyphenolic compounds are considered beneficial for human health. In this work, we investigated the polyphenol profile and antioxidant activity of edible tejocote (Crataegus pubescens) fruit extracts by micellar electrokinetic chromatography (MEKC) and HPLC/UV. The major phenolic compounds in the pulp extracts were (+)-catechin (9.17 ± 0.20 mg/100 mg dry fruit), (−)-epicatechin (4.32 ± 0.11 mg/100 mg dry fruit), and chlorogenic acid (5.60 ± 0.24 mg/100 mg dry fruit). The total phenolic content was 168.6 ± 0.9 mg gallic acid equivalent/g dry fruit; the total proanthocyanidin content was 84.6 ± 1.4 mg cyanidin/100 g dry fruit; and the total flavonoid content was 55.89 ± 1.43 mg quercetin/g dry fruit. Interestingly, procyanidins (dimers, trimers, and tetramers of (−)-epicatechin and (+)-catechin) were detected in the extract. This is the first study reporting the presence of polymeric polyphenols in Crataegus pubescens fruit. Accordingly, these fruits demonstrate great potential as a natural source of antioxidant phenolic compounds and could therefore be used as a nutraceutical and functional food.